2022
DOI: 10.3390/ma15062228
|View full text |Cite
|
Sign up to set email alerts
|

Cubic Iron Core–Shell Nanoparticles Functionalized to Obtain High-Performance MRI Contrast Agents

Abstract: Nanoparticles with SiO2 coating were synthesized to have a cubic iron core. These were found to have saturation magnetization very close to the highest possible value of any iron-containing nanoparticles and the bulk iron saturation magnetization. The in vitro toxicology studies show that they are highly biocompatible and possess better MRI contrast agent potential than iron oxide NPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…On account of biomarker-based diagnostic trends, groundbreaking nanotechnological research studies are being performed for entangling, detecting, and operating biomarkers for advanced therapeutics. , The designing of functional nanoprobes ensures specific and stable targeting for harvesting biomarkers through biosystems in a more precise manner. , Among various nanotechnological probes, iron oxide nanoparticles are classified as biomedical materials that are significantly employed for life science studies. , Iron is very important due to its incredible superparamagnetic and biocompatible nature, showing significant results for magnetic resonance imaging, targeted delivery of drugs, proteins, nucleic acids, and antibodies for hyperthermia biosensing, tissue repair, and separation of biomolecules. Furthermore, iron nanoparticles with different sizes, shapes, and high surface volume ratios that can also be controlled enhanced biomedical application results for challenging tasks. , Nanomaterials have encouraging physiochemical characteristics which have shown preclinical and clinical medical advances using iron oxide NPs for certain diagnostic probes. , Gold, zinc, copper, nickel, and SiO 2 have unique characteristics in biocompatibility, stability, surface area, size, morphology, and their interaction with the biological system, but iron nanoparticles possess excellent magnetic nature, high surface area, and electrical and thermal conductivity. There are many ways to prepared novel and innovative nanoparticles with unique surface modification for multiple applications in the field of agriculture, medical, and different industries .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On account of biomarker-based diagnostic trends, groundbreaking nanotechnological research studies are being performed for entangling, detecting, and operating biomarkers for advanced therapeutics. , The designing of functional nanoprobes ensures specific and stable targeting for harvesting biomarkers through biosystems in a more precise manner. , Among various nanotechnological probes, iron oxide nanoparticles are classified as biomedical materials that are significantly employed for life science studies. , Iron is very important due to its incredible superparamagnetic and biocompatible nature, showing significant results for magnetic resonance imaging, targeted delivery of drugs, proteins, nucleic acids, and antibodies for hyperthermia biosensing, tissue repair, and separation of biomolecules. Furthermore, iron nanoparticles with different sizes, shapes, and high surface volume ratios that can also be controlled enhanced biomedical application results for challenging tasks. , Nanomaterials have encouraging physiochemical characteristics which have shown preclinical and clinical medical advances using iron oxide NPs for certain diagnostic probes. , Gold, zinc, copper, nickel, and SiO 2 have unique characteristics in biocompatibility, stability, surface area, size, morphology, and their interaction with the biological system, but iron nanoparticles possess excellent magnetic nature, high surface area, and electrical and thermal conductivity. There are many ways to prepared novel and innovative nanoparticles with unique surface modification for multiple applications in the field of agriculture, medical, and different industries .…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 Among various nanotechnological probes, iron oxide nanoparticles are classified as biomedical materials that are significantly employed for life science studies. 5 , 6 Iron is very important due to its incredible superparamagnetic and biocompatible nature, showing significant results for magnetic resonance imaging, 7 targeted delivery of drugs, 8 proteins, nucleic acids, and antibodies for hyperthermia biosensing, tissue repair, and separation of biomolecules. 9 11 Furthermore, iron nanoparticles with different sizes, shapes, and high surface volume ratios that can also be controlled enhanced biomedical application results for challenging tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Based on its superparamagnetic properties, IONPs are usually used in MRI examinations and targeted to specific areas under the action of an external magnetic field to achieve targeted therapeutic effects ( Radeloff et al, 2020 ). Maria et al ( Volokhova et al 2022) made SiO 2 -coated magnetic iron oxide nanoparticles into α-Fe@SiO 2 with a cubic morphology, which exhibited higher MRI relaxation than iron oxide alone and could show high-performance contrast effects. Zheng et al (2022) found that allantoin phosphate can deliver iron oxide nanoparticles precisely to bone tissue for targeted synergistic treatment of osteoporosis.…”
Section: Iron Oxide Nanoparticles and Bone Regenerationmentioning
confidence: 99%